Konsentrasi Kepemilikan Media: Dampaknya Terhadap Pembatasan Keragaman Perspektif Publik di Masyarakat Modern Indonesia - Aminah Swarnawati; Makroen Sanjaya; Saiful Amir; Abd. Gani, Ahmad Yani (Jurnal Pewarta Indonesia, 2025)
Media ownership is a discussion that has always existed at any time. It is interesting to discuss because the theory is related to economics and politics. The diversity of perspectives is valuable as a bridge to society in consuming media information. Of course, it should be given freedom of space and access to concrete facts, instead of being confronted with the interests of power through capital owners to regulate the rotation of media issues according to the ruler's goals. The study in this research will discuss the influence of media ownership on the diversity of information and public perspectives in modern Indonesian society. The concentration of media ownership focuses on limiting the diversity of perspectives in a modern society that is instantaneous to obtain information, restrictions for reasons of political and industrial interests, the tendency of media ownership will be seen as domination. Using a qualitative approach and literature study, this research will analyze data from various sources to identify the impact of concentration of media ownership on access to public information, representation of the interests of various groups, and the role of the media as an information bridge. The results show that the concentration of media ownership creates a less diverse and less representative media ecosystem. This has a negative impact on the quality of democracy and people's ability to make rational decisions. By limiting the diversity of perspectives, concentration of media ownership creates a narrower and less inclusive public sphere.